Chitosan-Modified Biochar and Unmodified Biochar for Methyl Orange: Adsorption Characteristics and Mechanism Exploration - Nguyen Xuan Loc; Phan Thi Thanh Tuyen; Le Chi Mai; Do Thi My Phuong (Toxics, 2022)
In this study, shrimp shell-derived chitosan (CS) and rice husk-derived biochar (RHB) were produced; CS and RHB were then used to synthesize chitosan-modified biochar (CSBC) hydrogel beads. N2 adsorption (77K), SEM-EDX and FT-IR techniques were used to evaluate the physicochemical properties of the adsorbents. A batch experiment was conducted to test the methyl orange (MO) adsorption performance of RHB and CSBC. The results showed that the MO adsorption process was strongly pH-dependent. The kinetics were well described by the pseudo-second-order and intra-particle diffusion models, assuming the chemisorption and intraparticle diffusion mechanisms govern the adsorption process. Homogeneous adsorption for MO on the surface of RHB and CSBC was also assumed since the isotherm data showed the best-fit to the Langmuir model. Under the experimental conditions of initial pH 3, dosage 0.2 g, contact time 240 min and temperature 298 K, the maximum adsorption capacity of CSBC and RHB for MO dye adsorption was 38.75 mg.g−1 and 31.63 mg.g−1, respectively. This result demonstrated that biochar had better performance after modification with chitosan, which provided more functional groups (i.e., −NH2 and −OH groups) for enhanced electrostatic interactions and complexation between MO and CSBC. Overall, CSBC is an effective adsorbent for the removal of MO from aqueous solution.